Microstructure Analysis of Synthesized LiBOB - Etty Marti Wigayati; Christin Rina Ratri; Ibrahim Purawiardi; Fadli Rohman; Titik Lestariningsih (Indonesian Journal of Chemistry, 2015)
Lithium bis (oxalate) borate or LiBOB is an active material used as the electrolyte for lithium battery application. LiBOB (LiB(C2O4)2) powder was prepared from LiOH, H2C2O4 and H3BO3. The employed method was solid state reaction. LiBOB powder produced from the reaction was then observed using SEM and TEM. Surface area was analyzed using Quantachrome Nova 4200e. From the analysis analyzed using XRD to identify the resulting phases, crystal structure, and crystallite size. The functional groups were analyzed using FT-IR. The particle morphology was result, it was seen that the resulted phases were C4LiBO8 and LiB(C2O4)2.H2O, the crystal structure was orthorhombic with space group Pbca and Pnma. From the particle morphology observation it was shown that micro pores were created irregularly. When the observation was deepened, nanopores with elongated round shape were seen within the micropores. The pore size was approximately 50–100 nm. The surface area, total pore volume, and average pore diameter of LiBOB powder was 88.556 m2/g, 0.4252 cm3/g, and 19.2 nm respectively.